2018
DOI: 10.1111/ner.12746
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rate on Analgesia in Kilohertz Frequency Spinal Cord Stimulation: Results of the PROCO Randomized Controlled Trial

Abstract: ObjectiveThe PROCO RCT is a multicenter, double‐blind, crossover, randomized controlled trial (RCT) that investigated the effects of rate on analgesia in kilohertz frequency (1–10 kHz) spinal cord stimulation (SCS).Materials and MethodsPatients were implanted with SCS systems and underwent an eight‐week search to identify the best location (“sweet spot”) of stimulation at 10 kHz within the searched region (T8–T11). An electronic diary (e‐diary) prompted patients for pain scores three times per day. Patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
130
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(138 citation statements)
references
References 49 publications
(70 reference statements)
2
130
0
1
Order By: Relevance
“…In the context of kHz-SCS, this study specifically addressed joule heat with the hypothesis that by increased power (pulse compression), kHz-SCS waveforms will superlinearly increase tissue temperature, potentially inducing downstream alterations in tissue function with therapeutic effects in chronic pain. Characteristic clinical responses to kHZ-SCS including as the lack of associated neural sequelae such as paresthesia and the frequency insensitivity of efficacy 52 reconcile well with joule heating, while the delayed time course of effects 53 may be explain by temperature homeostatic responses or heat shock protein regulation of neuroinflammation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the context of kHz-SCS, this study specifically addressed joule heat with the hypothesis that by increased power (pulse compression), kHz-SCS waveforms will superlinearly increase tissue temperature, potentially inducing downstream alterations in tissue function with therapeutic effects in chronic pain. Characteristic clinical responses to kHZ-SCS including as the lack of associated neural sequelae such as paresthesia and the frequency insensitivity of efficacy 52 reconcile well with joule heating, while the delayed time course of effects 53 may be explain by temperature homeostatic responses or heat shock protein regulation of neuroinflammation.…”
Section: Discussionmentioning
confidence: 86%
“…heat shock proteins). Slow temperature homeostatic changes provide a plausible explanation for the delayed onset of pain relief by kHz-SCS 52,53 and suggest specific molecular pathways (MoA) for pain relief including heat shock protein producing downregulation of neuroinflammation. For example, 72-kDa heat shock protein (Hsp70) inhibits activation of the pro-neuroinflammatory transcription factor, nuclear factor-kB in satellite glial cells (NF-kB) 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Why this location is critical is unknown, and it was questioned in a recent clinical study that explored locations within the T8–T11 range using SCS at 10 kHz (Thomson et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that stimulation over a particular spinal segment is entirely empirical and that no clear mechanism has been proposed to explain the clinically observed effects of high‐frequency SCS, Thomson et al. () searched for the optimal stimulation location (‘sweet spot’) within the T8–T11 vertebral segments. Electrical bipoles were activated at 10 kHz, with a pulse width of 30 μs, and current amplitude titrated to optimize therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In the PROCO RCT by Thomson et al found in 20 patients, implanted with SCS systems, equal pain relief at 1 and 10 kHz. At 1 kHz significant less charge was needed compared to 10 kHz .…”
Section: Introductionmentioning
confidence: 99%